M. leprae inhibits apoptosis in THP-1 cells by downregulation of Bad and Bak and upregulation of Mcl-1 gene expression - Tayyebi Ali; Ashraf Mussarat; Hasan Zahra; Hussain Rabia (BMC Microbiology, 2006)
Abstract Background Virulent Mycobacterium leprae interfere with host defense mechanisms such as cytokine activation and apoptosis. The mitochondrial pathway of apoptosis is regulated by the Bcl-2 family of proteins. Expression of Fas ligand and apoptotic proteins is found in leprosy lesions and M. leprae has been shown to activate pro-apoptotic Bcl-2 genes, Bak and Bax. However, the mechanism by which M. leprae modulates apoptosis is as yet unclear. We investigated expression of apoptotic genes in THP-1 monocytes in response to infection by M. leprae and non-pathogenic M. bovis BCG. Results M. leprae did not induce apoptosis in THP-1 cells, while BCG induced a significant loss of cell viability by 18 h post-infection at both (multiplicity of infection) MOI-10 and 20, with an increase by 48 h. BCG-induced cell death was accompanied by characteristic apoptotic DNA laddering in cells. Non-viable BCG had a limited effect on host cell death suggesting that BCG-induced apoptosis was a function of mycobacterial viability. M. leprae also activated lower levels of TNF-alpha secretion and TNF-alpha mRNA expression than BCG. Mycobacterium-induced activation of apoptotic gene expression was determined over a time course of infection. M. leprae reduced Bad and Bak mRNA expression by 18 h post-stimulation, with a further decrease at 48 h. Outcome of cell viability is determined by the ratio between pro- and anti-apoptotic proteins present in the cell. M. leprae infection resulted in downregulation of gene expression ratios, Bad/Bcl-2 mRNA by 39% and Bak/Bcl-2 mRNA by 23%. In contrast, live BCG increased Bad/Bcl-2 mRNA (29 %) but had a negligible effect on Bak/Bcl-2 mRNA. Heat killed BCG induced only a negligible (1–4 %) change in mRNA expression of either Bak/Bcl-2 or Bad/Bcl-2. Additionally, M. leprae upregulated the expression of anti-apoptotic gene Mcl-1 while, BCG downregulated Mcl-1 mRNA. Conclusion This study proposes an association between mycobacterium-induced apoptosis in THP-1 cells and the regulation of Bcl-2 family of proteins. M. leprae restricts apoptosis in THP-1 cells by downregulation of Bad and Bak and upregulation of Mcl-1 mRNA expression.